MANAJEMEN SUMBER DAYA MANUSIA DALAM LEMBAGA EKONOMI SYARIAH - Anisa salsabila putri; Dewi Sartika; Zahara izzati; Adam damar putra (ICONS: Islamic Economics Journal, 2025)
Management is a branch of economics that plays an important role in the operational success of an organization or business. The application of business management can increase the effectiveness and efficiency of business or organizational resources to better achieve business goals or visions. Islam is a belief that is generally held by indonesian citizens and colors every aspect of the lives of its people, both in terms of belief, politics, social, and economic. As a result, employess are only objects of the company and not active paticipants in the development of the company where islamic HR management is implemented, then employess will become a subject of a company so that they can play an active role in the development of the company. The islamic economic system in managing HR is based on harmony or balance between material needs and human morals. The islamic economic system does not forget its main characteristic, namely human progress, depending on the degree of coordination and harmony between moral and material aspects.